Case Report: Telitacicept exposure in early pregnancy in a patient with SLE delivering an infant without any physical defect - Huang, Xiao-Shan; He, Zhong-yu; Wang, Shi-gang; Xu, Qiang; Lin, Chang-song (Frontiers in Medicine, 2026)
BackgroundSystemic lupus erythematosus (SLE) is a systemic autoimmune disorder characterized by inflammatory damage to multiple organs. Its incidence rate is relatively high among women of childbearing age. The use of biologics is not recommended during pregnancy in SLE patients; belimumab or rituximab may be considered selectively only during lactation. Telitacicept is a fusion protein composed of the extracellular domain of the transmembrane activator and CAML interactor (TACI)—a receptor for B-lymphocyte stimulator (BLyS)—and the Fc fragment of human IgG1. It was first approved in China in 2021 for the treatment of patients with active SLE. Currently, there is a lack of safety data on the use of telitacicept during pregnancy.Case presentationA 25-year-old woman with SLE was exposed to telitacicept during early pregnancy and delivered an infant without any physical defect. The patient was regularly receiving telitacicept injections. Her last dose was administered on 4 November 2024. Her last menstrual period was dated 7 November 2024, and telitacicept was discontinued upon pregnancy confirmation. During gestation, she was maintained on oral glucocorticoids, hydroxychloroquine, and tacrolimus. On 23 June 2025, at 32 weeks of gestation, she underwent a cesarean section due to “intrauterine growth restriction and preeclampsia” and delivered a male infant without any physical defects.ConclusionThis case suggests that exposure to telitacicept in the early stage of pregnancy did not result in structural defects in this case.